Leslie Marmon Silko and her Storyteller: An Autobiographical Collage - Dżurak, Ewa (Literatura Ludowa. Journal of Folklore and Popular Culture, 2025)
Leslie Marmon Silko published Storyteller in 1981 (second edition 2012). This is Silko’s first work translated into Polish, under the title Opowiadaczka z Puebla Laguna (2024). The format of this unusual book easily escapes genre classification. Here it is called the autobiographical collage. The selection contains 8 short stories, more than 20 poems, over 20 short prose texts and 26 black and white photos. The elements are tied together strongly, but not explicitly. The structure resembles a spider web, with radials coming out of the center connected by concentric spiral threads. The book is a homage to the storytelling tradition of Laguna Pueblo and its culture. This article aims to familiarize the reader with Leslie Marmon Silko, since it is the first time, this author has been translated into Polish as well as to present the book and its possible readings, and to show some of the translating issues.